An Aligned Poly(3-hydroxybutyrate-co-3-hydroxyvalerate) Scaffold Fixed with Fibronectin to Enhance the Attachment and Growth of Human Endothelial Progenitor Cells - Hsu, Chien-Ning; Lin, Ya-Ting; Chen, Yu-Hsu; Tseng, Tsung-Yu; Tsai, Hsing-Fen; Hong, Shinn-Gwo; Yao, Chao-Ling (Biotechnology and bioprocess engineering, 2023)
Repair and regeneration of vascular tissue is a crucial current research focus in the fields of biomedical engineering and regenerative medicine. Numerous studies revealed that cells are required to grow on an appropriate extracellular matrix to maintain or enhance functionality. In the present study, various surface modification methods were evaluated to fix fibronectin on the surface of a bio-based and aligned poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) film for vascular tissue engineering. After chemical modification, the properties of the fibronectin-fixed PHBV films were examined and compared with the original films, including -NH 2 group expression, contact angle, mechanical properties, and fibronectin binding amount. Then, cytotoxicity and biocompatibility were measured by culture with L929 cells and endothelial progenitor cells (EPCs) of the fibronectin-fixed PHBV films. In addition, cell morphology, cell growth kinetics, acetylated low-density lipoprotein uptake ability, lectin binding ability and specific gene expressions of cultured EPCs on fibronectin-fixed PHBV films were also analyzed. Taken together, our data demonstrated that the surface of the aligned PHBV films could be successfully modified to immobilize fibronectin. Importantly, EPCs cultured on the fibronectin-fixed PHBV films showed excellent cell biocompatibility, a rapid proliferation rate, an aligned growth direction and correct cell functions. We believed that fibronectin-fixed PHBV films can serve as a potential scaffold for vascular tissue engineering.